2001
DOI: 10.1021/om000932b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Effects in Ligand Substitution at a Transient Organometallic Species:  The Reaction of W(CO)5(Cyclohexane) with (CH3)nTHF and (CH3)nFuran (n = 1, 2)

Abstract: Time-resolved infrared absorption spectroscopy is used to study the reactions of the solvated transient intermediate W(CO)5(cyclohexane) with the molecules (L) 2-methyltetrahydrofuran (MeTHF), 2,5-dimethyltetrahydrofuran (Me2THF), 2-methylfuran (MeFur), and 2,5-dimethylfuran (Me2Fur). In all four cases, the only reaction observed on the microsecond to millisecond time scale is substitution of the cyclohexane molecule to form W(CO)5(L). From the temperature dependence of the reaction rate constant, measured ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…We chose to study linkage isomerization of M(CO) 5 (MeDHF) because, on one hand, η 1 -MeDHF should be a stronger electron donor than η 1 -2,3-DHF, and hence more reactive toward reaction 1, which on the other, the additional steric crowding in the η 1 -MeDHF complex might slow the reaction instead. We have observed such competition between steric and electronic factors in the ligand substitution reactions of the transient complex W(CO) 5 (CyH) with 2-methylfuran and 2,5-dimethylfuran, and Stringfield and Shepherd reported that the preferred coordination geometry of aminopyridines to W(CO) 5 (both the kinetic product distribution and the thermodynamically favored linkage isomer) depends on a finely tuned balance of electronic and steric factors . Our study of reaction 1 with L = DHP was motivated by our desire to learn what influence (if any) the size and structure of the C n H 2 n -2 O ring have on the kinetics and thermodynamics of the linkage isomerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to study linkage isomerization of M(CO) 5 (MeDHF) because, on one hand, η 1 -MeDHF should be a stronger electron donor than η 1 -2,3-DHF, and hence more reactive toward reaction 1, which on the other, the additional steric crowding in the η 1 -MeDHF complex might slow the reaction instead. We have observed such competition between steric and electronic factors in the ligand substitution reactions of the transient complex W(CO) 5 (CyH) with 2-methylfuran and 2,5-dimethylfuran, and Stringfield and Shepherd reported that the preferred coordination geometry of aminopyridines to W(CO) 5 (both the kinetic product distribution and the thermodynamically favored linkage isomer) depends on a finely tuned balance of electronic and steric factors . Our study of reaction 1 with L = DHP was motivated by our desire to learn what influence (if any) the size and structure of the C n H 2 n -2 O ring have on the kinetics and thermodynamics of the linkage isomerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, neither furan nor 2‐methylfuran produces [W(CO) 4 (η 4 ‐L)] under the experimental conditions that yield [W(CO) 4 (Me 2 Fur)] 2 within several seconds of the initial photolysis. We have previously noted that more strongly electron‐donating ligands tend to react more rapidly with [W(CO) 5 (CyH)] because they can more readily stabilize the transition state for the ligand exchange 11b,c. Presumably, similar considerations are at work in the present case.…”
mentioning
confidence: 56%
“…We have previously reported11c that in the presence of excess Me 2 Fur, [W(CO) 5 (CyH)] (CyH=cyclohexane) reacts rapidly (second‐order rate constant of 2.46×10 6 L mol −1 s −1 at 20 °C) to form [W(CO) 5 (Me 2 Fur)]. Based on the similarity of the C–O stretching region of its IR spectrum (two strong stretches at 1927 and 1941 cm −1 and a weak one at 2075 cm −1 ) to those of other [W(CO) 5 L] complexes (L=cyclic ether),11c we assigned to it the η 1 structure 1 , that is, the ligand is bound to the metal through the lone pair of the O atom. We also determined the activation parameters for the reaction to be Δ H ≠ =26.4±1.7 kJ mol −1 and Δ S ≠ =−41.0±4.2 J mol −1 K −1 .…”
mentioning
confidence: 99%
“…Moreover, Schultz has investigated furan and pyran isomerizations (η 1 -bonding through oxygen to and from η 2 -bonding of the double bond) on M­(CO) 5 centers (M = Cr, Mo, or W). For Mo­(CO) 5 (2,3-dihydrofuran), Δ S ⧧ = −2.6 J mol –1 K –1 for the η 1 → η 2 isomerization. Small negative activation entropies seem to be a general result for these types of reactions, and they suggest that the metal center “walks” around the periphery of the furan to coordinate the double bond following visible excitation. Similarly, Burkey and co-workers interpret the observed activation parameters for an intramolecular pyridine for ketone exchange as evidence that the ligand does not fully dissociate from the metal (a derivatized CpMn center), and that it is loosely bound as it migrates from the nitrogen (pyridine) to oxygen (ketone) .…”
Section: Resultsmentioning
confidence: 99%